Removal of pastor when parish is suppressed: Canons 538 and 1740-1747 - Paprocki, Thomas John (CLSA advisory opinions, 2001-2005, 2004)
Two parishes here in our diocese are being merged into one parish. After consulting the presbyteral council, the bishop is suppressing both parish "A" and parish "B" and then erecting a new parish. The pastor of parish "A" is retiring. What is the status of the pastor of parish "B"? He has indicated he wants to remain, becoming the pastor of the newly erected parish. The bishop feels this is not in the best interest of the community, however. Does the pastor have to resign? If he refuses to do so, does the bishop have to follow the canonical procedures for the removal of a pastor? Or, by the suppression of his parish, has his office simply ceased to exist?